Toss differences between the slice serve and the kick serve in tennis - Jan Carboch; Vladimír Süss (Palacký University Olomouc, 2015)
Background: Pre-contact information of servers' motion is important for receiving players in tennis. Objective: The aim of this study is to examine whether serving players use the same ball toss for kick serve (KS) and slice serve (SS) at two different directions of serves, from the receiver's view. Methods: 10 male right-handed professional tennis players with an average ATP ranking of 533 were videotaped from the receiver's view using a high-speed video camera (200 Hz). Firstly, they served SS and then KS from deuce court. After reaching 3 successful SS and 3 KS to the correct location, the same procedure followed from the ad court. Kinematic analysis was used to obtain the point of ball release, vertical toss peak and racquet-ball contact. Results: Even though the release point was found nearly in the same location, the vertical toss peak of KS was horizontally to the right compared to SS and the point of racquet ball-contact of KS was even more to the right by approximately 30 cm from the receiver's view. Similar findings were obtained from deuce court and ad court. Conclusions: We found differences in the ball toss execution between KS and SS. The serve toss can provide useful information for receiving players. Serving players should use the same toss for each type of serve to hide their intention.